Dynamic Inductor Switching and Frequency Control to Enhance Efficiency in Buck Converters for CubeSat EPS - Francesco Rocco Nardelli; Giuseppe Coviello; Giuseppe Brunetti; Caterina Ciminelli (IEEE Access)
The Electrical Power System (EPS) is a critical satellite subsystem that must meet mission requirements to operate effectively and ensure mission success, including supporting various operational modes during the required satellite lifetime. The power distribution of an EPS relies on Point of Load (POL) converters, which supply energy to all other subsystems. The efficiency of these DC/DC converters is crucial, especially when the satellite depends solely on batteries. High-efficiency converters help to minimize power losses, thereby potentially reducing the required battery size. This is particularly important for nanosatellite standardized platforms like CubeSats, which have strict limitations on space and weight. This paper introduces a versatile POL converter architecture based on switched inductors and switching frequency adjustment, aiming to optimize efficiency under different operating conditions. The effectiveness of the proposed method is demonstrated through a measurement campaign, and the preliminary results show that, with the proposed method, the converter can adapt its efficiency under both heavy and light load conditions. Our method exhibits an efficiency enhancement up to more than 25% compared to solutions that are based on the standard circuit parameters sizing, providing notable advantages for applications where power consumption is critical.